2014
DOI: 10.1016/j.neuroscience.2014.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Social regulation of adult neurogenesis in a eusocial mammal

Abstract: The present study examined social status and adult neurogenesis in the naked mole rat. These animals live in large colonies with a strict reproductive dominance hierarchy; one female and 1-3 males breed, while other members are subordinate and reproductively suppressed. We examined whether social status affects doublecortin (DCX; a marker for immature neurons) immunoreactivity in the dentate gyrus, piriform cortex (PCx), and basolateral amygdala (BLA) by comparing breeders to subordinates. We also examined sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 124 publications
(134 reference statements)
3
22
1
Order By: Relevance
“…Thus the rate of neurogenesis appears to progressively decrease as the level of dominance increases. Our findings are in agreement with findings in laboratory-bred naked molerats, the breeding animals, in particular the queens, were found to have a reduced number of young neurons compared to non-breeding subordinate colony members (Peragine et al, 2014).…”
Section: Effect Of Social Status On Neurogenesissupporting
confidence: 92%
See 1 more Smart Citation
“…Thus the rate of neurogenesis appears to progressively decrease as the level of dominance increases. Our findings are in agreement with findings in laboratory-bred naked molerats, the breeding animals, in particular the queens, were found to have a reduced number of young neurons compared to non-breeding subordinate colony members (Peragine et al, 2014).…”
Section: Effect Of Social Status On Neurogenesissupporting
confidence: 92%
“…Nonetheless, Bennett showed that testosterone levels do not differ between males in Damaraland mole-rat colonies (Bennett, 1994). Peragine and colleagues found no relationship between gonadal hormones and neurogenesis in the naked mole-rat (Peragine et al, 2014). The combined findings of our study and that of the naked mole-rats suggest that the reduced neurogenesis in eusocial mole-rat species are unrelated to gonadal hormones.…”
Section: Effect Of Social Status On Neurogenesiscontrasting
confidence: 40%
“…In wild Namaqua rock mice, previous reproduction led to a permanent reduction in AHN. Females that had at least one pregnancy in the former breeding season show lower AHN than males ; mole-rat breeders are also lower in neurogenesis than nonbreeding individuals in the eusocial naked mole rats (Peragine et al 2014). Breeding pressure, combined with scarce nutrients during winter, might limit the recovery of AHN permanently.…”
Section: The Energetic Trade-off Under Natural Conditionsmentioning
confidence: 99%
“…AHN has been reported in three wild and laboratory-bred mole-rat species (Amrein et al 2014;Peragine et al 2014) of the Bathyergidae family, among them the naked mole rat (Heterocephalus glaber), and in the wild Gambian giant rat (Cricetomys gambianus, family Nesomyidae [Olude et al 2014]). …”
Section: Evidence Of Hippocampal Neurogenesis In the Order Rodentiamentioning
confidence: 99%
“…In colonies of up to 300 individuals, breeding is restricted to one dominant female (the queen) and one to three males, with other colony members being socially subordinate and reproductively suppressed. Though pronounced alterations in neural and endocrine function accompany the change (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), male and female subordinates are capable of transitioning to breeding status following the death/removal of breeders or separation from the colony. Indeed, although colony-housed subordinates have low progesterone (P), testosterone (T), and luteinizing hormone (LH) concentrations compared with same-sex breeders (37,38), they show elevated urinary P and T levels within 1 wk of separation from the colony (37,40), with females developing a perforated vagina during that time (37).…”
mentioning
confidence: 99%